2020
DOI: 10.1159/000509015
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypothyroidism due to a Low Level of Maternal Thyrotropin Receptor-Blocking Antibodies

Abstract: <b><i>Introduction:</i></b> Maternal TSH receptor antibodies (TRAbs) can cross the placenta and affect fetal and neonatal thyroid function. Maternal TSH receptor-blocking antibodies (TBAbs) are a rare cause of congenital hypothyroidism. <b><i>Case Report:</i></b> Following the discovery of a highly elevated TSH on her neonatal screening test, a 10-day-old girl with no familial history of thyroid disorder was referred to the pediatric endocrinology unit. Hypothyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Regardless of the cause of CH, it is necessary to treat it in time once it is diagnosed so that the child's FT4 level reaches the normal range as soon as possible to meet the needs of growth and development [ 20 ], and most studies show that after active treatment, most children have a good prognosis and can reach the normal level of intelligence. However, a few children have neurological sequelae despite long-term, regular treatment, which may be related to maternal hypothyroidism and impaired neurological development during intrauterine fetal brain development during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the cause of CH, it is necessary to treat it in time once it is diagnosed so that the child's FT4 level reaches the normal range as soon as possible to meet the needs of growth and development [ 20 ], and most studies show that after active treatment, most children have a good prognosis and can reach the normal level of intelligence. However, a few children have neurological sequelae despite long-term, regular treatment, which may be related to maternal hypothyroidism and impaired neurological development during intrauterine fetal brain development during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pathogenic variants in TSHR and PAX8 genes have been reported in patients with permanent congenital hypothyroidism showing reduced to normal-sized eutopic thyroid glands with low to absent radioiodide uptake on thyroid scintigraphy ( 29 , 30 ). Regarding the patient with transient congenital hypothyroidism, Castellnou et al ( 31 ) recently reported a case of transient congenital hypothyroidism with eutopic gland and undetectable radioiodide uptake on thyroid scintigraphy due to maternal thyrotropin receptor-blocking antibodies (TRAbs). This report highlights the importance to analyze TRAbs in hypothyroid mothers during pregnancy, which is particularly useful when congenital hypothyroidism is diagnosed in their newborns.…”
Section: Discussionmentioning
confidence: 99%
“…TSH receptor-stimulating antibodies and TSH receptor-blocking antibodies are the two types of TSH receptor antibodies. The capacity of maternal TSH receptor antibodies to penetrate the placenta results in impaired fetal thyroid function [24]. Figure 2 depicts thyroid hormone regulation in the thyroid gland of the fetus.…”
Section: Thyroid Hormone In Fetal Developmentmentioning
confidence: 99%